spp.as biocontrol agents of post-harvest fungal decay in fruits and vegetables: mechanisms of action, challenges and opportunities - Leidoh Marcellin Akpafi; Wenwen He; Guanghao Li; Chenyang Zhu; Mengyue Wu; Yun Wang (BioControl, 2026)

Synergistic effects of nucleopolyhedroviruses on larvicidal activity against Spodoptera litura and Helicoverpa armigera - Zihan Shi; Jing Li; Can Wang; Shaolong Wu; Wei-ai Zeng; Shiping Jia; Yusheng Wang; Yansong Xiao; Mi Li; Lin Tan (BioControl, 2026)

Biocontrol of the black-spot disease pathogen (Alternaria alternata) in Dioscorea opposita by native endophytic bacterium Bacillus sp. E-Do8 - Chaochuang Li; Longlong Ma; Houmin Wang; Shunpeng Li; Ruifei Wang; Hao Zhang; Mingjun Li; Qingxiang Yang (BioControl, 2025)

Endophytic Beauveria bassiana promotes sunflower growth and confers resistance against sclerotinia disease - Li Sui; Yang Lu; Huiping Yang; Zhiming Liu; Li Wang; Xiaowei Zou; Qiyun Li; Zhengkun Zhang (BioControl, 2025)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Silage pathogens and biological control agents: effects, action mechanisms, challenges and prospects - Huifang Jiang; Charles Obinwanne Okoye; Yanfang Wu; Lu Gao; Xia Li; Yongli Wang; Jianxiong Jiang (BioControl, 2024)

Pseudomonas fluorescens HC1-07 transformed with phenazine-1-carboxylic acid biosynthesis genes has improved biocontrol activity against Rhizoctonia root rot and Fusarium crown rot of wheat - Quan Zeng; Chao Cui; Kaiyue Wang; Fang Li; Chenyang Li; Shanshan Wen; Mingming Yang (BioControl, 2023)

Which molecular marker is better? Comparative analyses of COI and ITS2 in molecular identification of Trichogramma (Hymenoptera: Trichogrammatidae) - Ao-Kai Wang; Fang-Yi Li; De-Sen Wang; Yu-Rong He; Yuan-Xi Li; Zhi-Chao Yan (BioControl, 2023)

Pathogenicity characteristics of the entomopathogenic fungus Cordyceps javanica IJ-tg19 to Acyrthosiphon pisum - Di Wang; Pei-Xiang Xing; Hong-Liang Diao; Wen-Wen Zhou; Xian-Wei Li; Li-Jun Zhang; Rui-Yan Ma (BioControl, 2023)

Assessment of Beauveria bassiana for the biological control of corn borer, Ostrinia furnacalis, in sweet maize by irrigation application - Mengxia Feng; Yunyue Zhang; Brad Steven Coates; Qian Du; Yuebo Gao; Lili Li; Haibin Yuan; Wei Sun; Xue Chang; Shuxiang Zhou; Yangzhou Wang (BioControl, 2023)
Kernels of sweet maize are directly consumed by humans. This high value crop is grown in arid and semi-arid regions of western Jilin Province, China where trickle irrigation is widely used and larvae of the corn borer, Ostrinia furnacalis Guenée (Lepidoptera: Crambidae), can cause significant kernel damage. Low humidity in arid regions is less conducive to the efficacy of the biological control agent, Beauveria bassiana (Balsamo) Vuillemin (Hypocreales: Cordycipitaceae). Simulated semi-arid conditions in greenhouse experiments were conducted comparing B. bassiana application on a granule carrier or in aqueous suspension to sweet maize. Applications of B. bassiana adhered to granules and in suspension reduced O. furnacalis leaf feeding damage, number of boreholes and tunneling length. Treatments with a granular carrier showed the most significant reductions in maize damage when applied once at whorl stage and in combination with a second application at the ear. The greatest reductions in boring and tunneling attributed to these treatments occurred at internodes around the ear. Although reduced damage was greatest following granular compared to aqueous applications, the latter also provided significant reductions in feeding damage compared to controls. This study demonstrates the utility of B. bassiana as a biological control agent for the reduction in damage caused by second-generation corn borer to sweet maize and existing irrigation equipment could be adapted for efficacious aqueous treatments by growers.

Enhanced expression of DNA methyltransferase 1-associated protein1 gene thermotolerance in a high-temperature acclimated predatory mite Neoseiulus barkeri - Ya-Ying Li; Chuan-Bei Tian; Yi-Xia Wu; Tian-Di Niu; Hao Wang; Wen-Hui Fan; Huai Liu (BioControl, 2021)

Reduction of soil-borne pathogen Fusarium solani reproduction in soil enriched with phenolic acids by inoculation of endophytic fungus Phomopsis liquidambari - Xing-Guang Xie; Chuan-Chao Dai; Xiao-Gang Li; Jia-Rui Wu; Qing-Qian Wu; Xing-Xiang Wang (BioControl, 2017)

Evaluation of Blattisocius dolichus (Acari: Blattisociidae) for biocontrol of root-knot nematode, Meloidogyne incognita (Tylenchida: Heteroderidae) - Chun-Ling Xu; Yong-Liang Chen; Xue-Nong Xu; Dong-Wei Wang; Hui Xie; En-Dong Wang; Dun-Song Li; Bao-Xin Zhang; Hou-Guo Qin (BioControl, 2014)

Biocontrol of Fusarium wilt disease in muskmelon with Bacillus subtilis Y-IVI - Qingyun Zhao; Wei Ran; Hui Wang; Xiang Li; Qirong Shen; Shengyuan Shen; Yangchun Xu (BioControl, 2013)

Vulnerability window for laying male eggs and superparasitism in producing female offspring of Encarsia sophia on Bemisia tabaci B biotype - Ting-Hui Chen; Min Li; Ji-Hong Wang; Fan Zhang; Yuan-Xi Li (BioControl, 2013)

Biological control of the pinewood nematode Bursaphelenchus xylophilus by application of the endoparasitic fungus Esteya vermicola - Chun Yan Wang; Zhe Ming Fang; Zhen Wang; Dong Liang Zhang; Li Juan Gu; Mi Ra Lee; Lei Liu; Chang Keun Sung (BioControl, 2011)

Effects of predator-mediated apparent competition on the population dynamics of Tetranychus urticae on apples - Chang-zhong Liu; Lin Yan; Hua-rong Li; Gang Wang (BioControl, 2006)